Revolution in science - Cohen, I. Bernard (Belknap Press of Harvard University Press, 1985)
Only a scholar as rich in learning as I. Bernard Cohen could do justice to a theme so subtle and yet so grand. Spanning five centuries and virtually all of scientific endeavor, Revolution in Science traces the nuances that differentiate both scientific revolutions and human perceptions of them, weaving threads of detail from physics, mathematics, behaviorism, Freud, atomic physics, and even plate tectonics and molecular biology, into the larger fabric of intellectual history.